Effect of organic acid treatment on the properties of rice husk silica - S. CHANDRASEKHAR, P. N. PRAMADA, L. PRAVEEN (JOURNAL OF MATERIALS SCIENCE 40 (2005) 6535-6544, 2005)
Rice husk, an agro waste material, contains about 20 per cent ash which can be retrieved as amorphous, chemically reactive silica. This silica finds wide applications as filler, catalyst/catalyst support, adsorbent and a source for synthesizing high performance silicon and its compounds. Various metal ions and unburned carbon influence the purity and color of the ash. Controlled burning of the husk after removing these ions can produce white silica of high purity. The present paper deals with the investigation carried out on two rice husk samples of different origin, one from the state of Andhra Pradesh (APRH) in the central part of India and the other from Kerala (KRH) the southern most part of the country. Leaching the husk with acetic and oxalic acids was attempted for the first time and the improvement in properties of the ash was studied. The husk samples were also treated with hydrochloric and nitric acids of different concentrations for comparison. The ashes produced by controlled burning of these samples before and after acid treatment, were characterized for the optical properties in addition to the chemical and physical nature. The APRH ash was found to be inferior to the KRH ash in all properties. Pretreatment of the husks with the organic acids improved the properties of ashes and the effect was comparable to that achieved by mineral acid leaching. Amorphous, reactive and high purity silica with high surface area and pore volume and good optical properties could be prepared from both the husks under specific conditions.